2017
DOI: 10.3390/ijerph14101250
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Environmental Correlates to Quality of Life in Park Users in Colombia

Abstract: Purpose: To explore individual and environmental correlates to quality of life (QoL) in park users in Colombia. Methods: A cross-sectional study with face-to-face interviews was conducted with 1392 park users from ten parks in Colombia. The survey included sociodemographic questions, health condition assessed with EuroQuol-5-Dimensions-5-Levels; in addition, questions about accessibility to the parks and perceptions about quality of infrastructure and green areas were asked. The Spanish version of the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 28 publications
0
39
0
2
Order By: Relevance
“…This review also informs how green space may relate to public health concerns in Global South countries, where, due to increasing urbanization [39], such challenges are multifaceted and complex. These concerns have been in part attributed to environmental stressors [39] resulting from inadequate environmental regulation and policy [120].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This review also informs how green space may relate to public health concerns in Global South countries, where, due to increasing urbanization [39], such challenges are multifaceted and complex. These concerns have been in part attributed to environmental stressors [39] resulting from inadequate environmental regulation and policy [120].…”
Section: Discussionmentioning
confidence: 99%
“…These concerns have been in part attributed to environmental stressors [39] resulting from inadequate environmental regulation and policy [120]. In particular, air pollution is of extreme concern in Global South cities [121], and studies found that it is linked to cardiovascular and respiratory-related mortality [122], poor maternal outcomes [123], cancer rates and immune system dysfunctions [124].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These contextual factors are such as rural and urban/metropolitan areas [ 9 , 10 , 11 ] and population density [ 3 , 12 , 13 , 14 ]. It has been clearly shown that people’s relation to their living environments is a key issue in their quality of life [ 12 , 15 , 16 , 17 , 18 ]. Well-designed housing has been identified as an important factor in promoting quality of life [ 19 ].…”
Section: Introductionmentioning
confidence: 99%